The impact of psychoeducation, nutrition, and dental health management on parental knowledge, attitudes, and behaviours in caring for autistic children - Arnela Nur; Sisca Mardelita; Intan Liana; Cut Ratna Kemala; Linda Suryani; Nunung Sri Mulyani (AcTion: Aceh Nutrition Journal, 2024)
The number of children with autism in Indonesia continues to increase annually. Children with autism often eat sweet and sticky foods, have irregular brushing habits, and rarely receive parental guidance for maintaining oral health. This is certainly a trigger for stunting in children. Preventive efforts include providing psychoeducation to parents or caregivers. This study aimed to improve the knowledge, attitudes, and behavior of parents or caregivers of children with autism. The research design was a quasi-experiment with pre-test and post-test non-equivalent group designs. This study was conducted at the School for Students with Special Needs (SLB) and SLB in Pembina Aceh Province, involving 25 parents/caregivers of children with autism (intervention group) and 17 parents/caregivers in the control group. Data were collected through interviews, using questionnaires. Data were analyzed using the Mann-Whitney and Wilcoxon tests, The results showed that nutritional management psychoeducation had an effect on knowledge, attitudes, and behavior (p<0,05), whereas the control group showed no difference in behavior (p>0,05). Furthermore, nutritional management psychoeducation was effective in improving parents' knowledge, attitude, and behavior (p=0,001) compared to the control group. In conclusion, nutritional management psychoeducation significantly improved parents' knowledge, attitudes, and behaviors. This intervention proved to be more effective than that in the control group.